Body mass index in HER2-negative metastatic breast cancer treated with first-line paclitaxel and bevacizumab. Issue 4 (3rd April 2018) - Pizzuti, Laura; Sergi, Domenico; Sperduti, Isabella; Lauro, Luigi Di; Mazzotta, Marco; Botti, Claudio; Izzo, Fiorentino; Marchetti, Luca; Tomao, Silverio; Marchetti, Paolo; Natoli, Clara; Grassadonia, Antonino; et al.
ABSTRACT: The evidence emerged from the TOURANDOT trial encourages evaluating the role of anthropometric determinants on treatment outcomes in HER2-negative metastatic breast cancer patients treated with bevacizumab-including regimens. We thus analyzed data from a subgroup of these patients from a larger cohort previously assessed for treatment outcomes. Patients were included in the present analysis if body mass index values had been recorded at baseline. Clinical benefit rates, progression free survival and overall survival were assessed for the overall study population and subgroups defined upon molecular subtype. One hundred ninety six patients were included (N:196). Body mass index showed no impact on clinical benefit rates in the overall study sample and in the luminal cancer subset (p = 0.12 and p = 0.79, respectively), but did so in the triple negative subgroup, with higher rates in patients with body mass index ≥25 (p = 0.03). In the overall study sample, body mass index did no impact progression free or overall survival (p = 0.33 and p = 0.67, respectively). Conversely, in triple negative patients, progression free survival was significantly longer with body mass index ≥25 (6 vs 14 months, p = 0.04). In this subset, overall survival was more favorable (25 vs 19 months, p = 0.02). The impact of the molecular subtype was confirmed in multivariate models including the length of progression free survival, and number of metastatic sites (p < 0.0001). Further studies are warranted to confirm our findings in more adequately sized, ad hoc, prospective studies.